[OP.3C.02] LOOKING FOR THE OPTIMAL BLOOD PRESSURE VALUES IN OLD PEOPLE WITH COGNITIVE DECLINE: A LONGITUDINAL STUDY BASED ON 24-HOUR AMBULATORY BLOOD PRESSURE MONITORING. (September 2016) - Lorenzi, C.; Mossello, E.; Giuliani, E.; Nesti, N.; Bulgaresi, M.; Caleri, V.; Pieraccioli, M.; Tonon, E.; Cavallini, M.C.; Baroncini, C.; Di Bari, M.; Biagini, C.A.; et al.
Abstract : Objective: Available data on the prognostic role of blood pressure in older subjects with cognitive impairment are still scarce. We recently showed that tight control of blood pressure may be associated with a greater progression of cognitive impairment in the short term. Aim of this study is to evaluate the long term association of clinical and ambulatory blood pressure (BP) and antihypertensive drugs (AHD) with survival and desease progression in older subjects with cognitive impairment. Design and method: We enrolled 198 subjects (average age 79, 72% with high BP) with Mild Cognitive Impairment (39%) or dementia (61%) referred to the memory clinic. Each patient underwent cognitive assessment with Mini Mental State Examination (MMSE) and 24-hour blood pressure monitoring (ABPM). Subjects were divided into tertiles according to the values of systolic (SBP) and diastolic (DBP) blood pressure, assessed both clinically and by ABPM (mean daytime and night-time). Results: After a mean 3-year follow-up, an independent association was observed between higher night-time SBP (> 135 mmHg) and mortality (p < 0, 001), after adjustment for age, vascular comorbidity and functional status. A similar, although weaker association was observed for higher night-time DBP and daytime SBP. Conversely, MMSE decline was greater in patients with lower daytime SBP (< 128 mmHg) (p = 0.029), but limited to the subgroup of subjects receiving AHD (p = 0.002), independently of age, vascular comorbidity and baseline MMSE score. No significant association was observed for clinical SBP. Conclusions: In this study higher mean SBP, especially at night, was predictive of mortality at 3 years, while lower average daytime SBP in subjects receiving AHD was associated with progression of cognitive impairment. High-normal SBP values (130–145 mmHg) seem to be the optimal target to reduce the risk of mortality and the progression of cognitive decline among cognitively impaired older subjects. ABPM is needed for BP assessment in this vulnerable population.